Scandium-based MOF (Metal Organic Framework) crystal material as well as preparation method and application thereof

By designing a scandium-based MOF crystal material constructed by self-assembly of [Sc3(μ2-OH)3(CO2)4O6]n inorganic metal chain and 2,5-thiophene dicarboxylic acid and nitrate ions, the problem of insufficient selectivity and stability of existing MOFs materials when separating C2H6 and C2H4 is solved, and the effect of efficient separation and recovery of light hydrocarbons in MTO technology is achieved.

CN119823406AActive Publication Date: 2025-04-15ARMY ENG UNIV OF PLA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510029976.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

Existing MOFs materials have insufficient selectivity and stability when separating C2H6 and C2H4, which is difficult to meet the needs of efficient separation and recovery of light hydrocarbons in MTO technology.

Method used

A scandium-based MOF crystal material constructed from self-assembly of [Sc3(μ2-OH)3(CO2)4O6]n inorganic metal chains and 2,5-thiophene dicarboxylic acid and nitrate ions is designed, with excellent thermal stability, water stability, solvent stability and wide pH stability.

Benefits of technology

The material preferentially adsorbs C3H6 at normal temperature and pressure, then C2H6, and finally C2H4, with good separation performance of C3H6/C2H4 and C2H6/C2H4, and can effectively separate C2H4 and C2H6, thereby obtaining high-purity C2H4 and recovering C3H6.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823406A_ABST
    Figure CN119823406A_ABST
Patent Text Reader

Abstract

The invention discloses a scandium-based MOF crystal material as well as a preparation method and application thereof. The MOF crystal is of a three-dimensional porous frame structure formed by mutual connection of [Sc3 (mu2-OH) 3 (CO2) 4O6] n inorganic metal chains, 2, 5-thiophenedicarboxylic acid and nitrate ions, ligand 2, 5-thiophenedicarboxylic acid is used as a platform and is directly synthesized with metal Sc through solvothermal reaction, reaction conditions are mild, and the method is simple and easy to implement. The MOF crystal has high crystallinity, excellent thermal stability, water stability and solvent stability and wide pH stability. According to the present invention, the C3H6, the C2H6 and the C2H4 are preferentially adsorbed under the normal temperature and the normal pressure, such that the good C3H6 / C2H4 and C2H6 / C2H4 separation performance is provided so as to obtain the high-purity C2H4 and recover the C3H6, and the method can be used for the effective separation of the C2H4 and the C3H6 in the methanol-to-olefin (MTO) mixture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of porous organic materials, and specifically relates to a porous organic material composed of [Sc3(μ2-OH)3(CO2)4O6] n Inorganic metal chains and organic ligand 2,5-thiophenedicarboxylic acid (H2Tdc) are constructed to form a porous scandium-based MOF crystalline material with excellent stability. Background Art

[0002] Ethylene (C2H4) and propylene (C3H6) are important basic raw materials for modern manufacturing and petrochemical products, and they occupy an important position in the petrochemical industry and energy field. Therefore, their demand is increasing year by year. At present, methanol to olefins (MTO) technology is the core technology for developing non-petroleum resources to produce light hydrocarbons such as C2H4 and C3H6, and has become the focus of development in recent years. In MTO products, the contents of C2H4 and C3H6 can reach 51.1wt% and 20.9wt%, respectively, but they inevitably contain ethane (C2H6, 6-10%) as the main impurity. Therefore, in order to obtain polymer-grade C2H4 and C3H6, it is crucial to efficiently separate C2H6 and C2H4 and recover C3H6. Due to the disadvantages of high energy consumption and high cost of traditional low-temperature distillation technology, the use of porous materials for adsorption separation technology is favored due to its advantages such as low energy consumption, high efficiency and flexible operation. Therefore, the development of new and efficient porous materials has become the core and key of adsorption separation technology.

[0003] Metal-Organic Framework (MOF), an emerging organic-inorganic hybrid material, is a porous crystalline material with a periodic network structure formed by self-assembly of metal ions or metal clusters and organic ligands. Due to its advantages such as high specific surface area and porosity, adjustable components and structure, it has broad application prospects in the field of gas adsorption and separation, and has become an ideal choice for purifying C2H4 by separating light hydrocarbon mixtures. At present, although a small number of MOFs adsorbents for separating C2H6 and C2H4 have been reported, they are still in the early stages of research and still have certain deficiencies in selectivity and stability (Small 2023, 19, 2300821. Chinese J. Chem. Eng. 2022, 42, 35-41.). Therefore, it is still a great challenge to design and synthesize new and efficient MOFs for the separation of C2H6 and C2H4 and the recovery of C3H6. Summary of the invention

[0004] The object of the present invention is to provide a stable scandium-based MOF crystal material. The scandium-based MOF crystal material has high crystallinity, excellent thermal stability, water stability, solvent stability and wide pH stability. At normal temperature and pressure, C3H6 is preferentially adsorbed, then C2H6, and finally C2H4, and has good C3H6 / C2H4 and C2H6 / C2H4 separation performance, and can well separate C2H4 and C2H6, thereby obtaining high-purity C2H4 and recovering C3H6, and the yields of C2H4 and C3H6 are 13.04L / kg and 28.01L / kg respectively.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] In a first aspect, the present invention provides a stable scandium-based MOF crystalline material, whose chemical formula is: {[Sc3(OH)2(Tdc)3(NO3)]·H2O} ∞ .

[0007] Furthermore, the scandium-based MOF crystal material is composed of [Sc3(μ2-OH)3(CO2)6O2] n A scandium-based MOF with a microporous structure is self-assembled by connecting inorganic metal chains with organic ligands 2,5-thiophenedicarboxylic acid and nitrate ions.

[0008] Furthermore, the [Sc3(μ2-OH)3(CO2)6O2] n There are two independent Sc ions in the inorganic metal chain, namely Sc1 and Sc2, both of which are hexacoordinated. The six coordinated oxygen atoms of Sc1 come from four different 2,5-thiophenedicarboxylic acid ligands, one μ2-OH and a nitrate ion; the six coordinated oxygen atoms of Sc2 come from four different 2,5-thiophenedicarboxylic acid ligands and two μ2-OH.

[0009] Furthermore, the scandium-based MOF crystal material belongs to the monoclinic crystal system and the I2 / m space group.

[0010] Furthermore, the crystallographic data of the scandium-based MOF crystal material are: unit cell parameters: α=90°, β=96.642(3)°, γ=90°, Z=4.

[0011] Furthermore, the scandium-based MOF crystal material is a colorless, transparent bulk crystal having excellent thermal stability, water stability, solvent stability and a wide range of pH stability.

[0012] In a second aspect, the present invention provides a method for preparing the stable scandium-based MOF crystal material described in the first aspect, which is directly synthesized by solvent thermal reaction of 2,5-thiophenedicarboxylic acid and metal Sc, and specifically comprises the following steps:

[0013] (1) Add 17.5 mg of the organic ligand 2,5-thiophenedicarboxylic acid and 10 mg of the template 1,2,4-triazole into 2.5 ml of acetonitrile and perform sonication for a period of time to fully mix the mixture, which is recorded as the first solution;

[0014] (2) Dissolve 46 mg of hydrated scandium nitrate in 1.8 ml of H2O, referred to as the second solution;

[0015] (3) mixing the first solution and the second solution, and then adding 60 to 90 μL of concentrated nitric acid to obtain a transparent mixed solution;

[0016] (4) placing the mixed solution in an oven for solvothermal reaction to obtain colorless transparent block crystals, which are scandium-based MOF crystal materials.

[0017] Furthermore, the solvent thermal reaction temperature was 100°C and the reaction time was 72h.

[0018] In a third aspect, the present invention further provides the use of the scandium-based MOF crystal material described in the first aspect in separating light hydrocarbon mixtures and purifying C2H4.

[0019] Compared with the prior art, the present invention has the following significant advantages:

[0020] 1. The scandium-based MOF crystal material provided by the present invention is directly synthesized by a simple solvent thermal reaction of 2,5-thiophenedicarboxylic acid and metal Sc, and the reaction conditions are relatively mild and simple and easy to operate.

[0021] 2. The scandium-based MOF crystal material provided by the present invention has high crystallinity, excellent thermal stability, water stability, solvent stability and wide pH stability, which is convenient for practical application research.

[0022] 3. The scandium-based MOF crystal material provided by the present invention preferentially adsorbs C3H6, then C2H6, and finally C2H4 at room temperature and pressure, and has good C3H6 / C2H4 and C2H6 / C2H4 separation performance, and can well separate C2H4 and C2H6, thereby obtaining high-purity C2H4 and recovering C3H6 in one step, and shows excellent application prospects in purifying C2H4 and recovering C3H6 in MTO mixtures. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is an optical microscope image of the scandium-based MOF crystal material of the present invention.

[0024] Figure 2 Schematic diagram of the structure of the scandium-based MOF crystal material of the present invention, wherein: (a) the coordination mode of the Sc1 atom; (b) the coordination mode of the Sc2 atom; (c) the one-dimensional metal chain [Sc3(μ2-OH)3(CO2)4O6] n (d) Schematic diagram of the three-dimensional network structure along the a-axis; (e) Schematic diagram of the three-dimensional network structure along the ac-axis.

[0025] Figure 3 This is the PXRD diagram of the scandium-based MOF crystal material of the present invention.

[0026] Figure 4 The PXRD diagrams of the scandium-based MOF crystal material of the present invention after being immersed in HCl and KOH aqueous solutions of different pH values ​​for 24 hours.

[0027] Figure 5 The PXRD diagrams of the scandium-based MOF crystal material of the present invention when immersed in water for different time periods.

[0028] Figure 6 The PXRD spectra of the scandium-based MOF crystal material of the present invention immersed in different organic solvents for 24 hours.

[0029] Figure 7 This is a thermogravimetric curve of the scandium-based MOF crystal material of the present invention.

[0030] Figure 8 It is the normal pressure isothermal adsorption curve of C2H4, C2H6 and C3H6 of the scandium-based MOF crystal material of the present invention at 288K.

[0031] Fig. 9 It is the normal pressure isothermal adsorption curve of C2H4, C2H6 and C3H6 of the scandium-based MOF crystal material of the present invention at 298K.

[0032] Fig.10 It is the normal pressure isothermal adsorption curve of C2H4, C2H6 and C3H6 of the scandium-based MOF crystal material of the present invention at 308K.

[0033] Fig.11 It is the adsorption enthalpy of C2H4, C2H6 and C3H6 of the scandium-based MOF crystal material of the present invention.

[0034] Fig.12 It is the adsorption selectivity of the scandium-based MOF crystal material of the present invention for the mixed gas C2H6 / C2H4 (v / v, 1 / 9) at 298K.

[0035] Fig.13 It is the adsorption selectivity of the scandium-based MOF crystal material of the present invention at a mixed gas of C3H6 / C2H4 (v / v, 2 / 5) at 298K.

[0036] Fig.14 It is the penetration curve of the scandium-based MOF crystal material of the present invention at 298K in a three-component gas mixture of C2H6 / C3H6 / C2H4 (2 / 10 / 25, v / v / v).

[0037] Fig.15 Shown is the analytical curve diagram of C2H4, C2H6 and C3H6 of the scandium-based MOF crystal material of the present invention at 338K (He purge rate 4 mL / min).

[0038] Fig.16 The following is a graph showing the analytical properties of the scandium-based MOF crystal material of the present invention at 338K for C3H6 (He purge rate 4 mL / min).

[0039] Fig.17 This is the PXRD pattern of the scandium-based MOF crystal material prepared in Example 2. DETAILED DESCRIPTION

[0040] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0041] 1. Sample preparation

[0042] The raw materials in the examples of the present application were purchased from commercial sources, for example, hydrated scandium nitrate (CasNo: 13465-60-6) was a MacLean brand chemical reagent.

[0043] Example 1

[0044] At room temperature, 2,5-thiophenedicarboxylic acid (17.5 mg) and 1,2,4-triazole (10 mg) were dissolved in 2.5 ml of acetonitrile (MeCN) solution, and ultrasonicated for 1 h to fully mix them to obtain a white suspension S1. Hydrated scandium nitrate (46 mg) was dissolved in 1.8 ml of H2O, and ultrasonicated to fully mix them to obtain a transparent colorless clear liquid S2. The S1 solution and the S2 solution were mixed, 40 μL of concentrated nitric acid was added, and the mixture was placed in an oven at 100 ° C for 72 h. Then the mixture was taken out and cooled to room temperature, and washed with MeCN. It was observed that a precipitate was deposited at the bottom of the reaction bottle, but no crystals were produced.

[0045] Example 2

[0046] At room temperature, 2,5-thiophenedicarboxylic acid (17.5 mg) and 1,2,4-triazole (10 mg) were dissolved in 2.5 ml of acetonitrile (MeCN) solution, and ultrasonicated for 1 h to fully mix them to obtain a white suspension S1. Hydrated scandium nitrate (46 mg) was dissolved in 1.8 ml of H2O, and ultrasonicated to fully mix them to obtain a transparent colorless clear liquid S2. The S1 solution and the S2 solution were mixed, 60 μL of concentrated nitric acid were added, and the mixture was placed in an oven at 100 ° C for 72 h. Then it was taken out and cooled to room temperature, and washed with MeCN. A small amount of colorless and transparent block crystals were observed to be deposited at the bottom of the reaction bottle. PXRD test showed that the crystals were scandium-based MOF crystal materials, such as Fig.17 shown.

[0047] Example 3

[0048] At room temperature, 2,5-thiophenedicarboxylic acid (17.5 mg) and 1,2,4-triazole (10 mg) were dissolved in 2.5 ml of acetonitrile (MeCN) solution, and ultrasonicated for 1 h to fully mix them to obtain a white suspension S1. Hydrated scandium nitrate (46 mg) was dissolved in 1.8 ml of H2O, and ultrasonicated to fully mix them to obtain a transparent colorless clear liquid S2. The S1 solution and the S2 solution were mixed, 90 μL of concentrated nitric acid were added, and the mixture was placed in an oven at 100 ° C for 72 h. Then it was taken out and cooled to room temperature, and washed with MeCN. A large number of colorless and transparent block crystals were observed to be deposited at the bottom of the reaction bottle. PXRD test showed that the crystals were scandium-based MOF crystal materials, such as Figure 3 shown.

[0049] Example 4

[0050] At room temperature, 2,5-thiophenedicarboxylic acid (17.5 mg) and 1,2,4-triazole (10 mg) were dissolved in 2.5 ml of acetonitrile (MeCN) solution, and ultrasonicated for 1 h to fully mix them to obtain a white suspension S1. Hydrated scandium nitrate (46 mg) was dissolved in 1.8 ml of H2O, and ultrasonicated to fully mix them to obtain a transparent colorless clear liquid S2. The S1 solution and the S2 solution were mixed, 110 μL of concentrated nitric acid was added, and the mixture was placed in an oven at 100 ° C for 72 h. Then it was taken out and cooled to room temperature, washed with MeCN, and no crystals were deposited at the bottom of the reaction bottle.

[0051] Example 5

[0052] At room temperature, 2,5-thiophenedicarboxylic acid (17.5 mg) was dissolved in 2.5 ml of acetonitrile (MeCN) solution, and ultrasonicated for 1 h to fully mix it to obtain a white suspension S1. Hydrated scandium nitrate (46 mg) was dissolved in 1.8 ml of H2O, and ultrasonicated to fully mix it to obtain a transparent colorless clear liquid S2. The S1 solution and the S2 solution were mixed, 90 μL of concentrated nitric acid were added, and placed in a 100 ° C oven for 72 h. Then it was taken out and cooled to room temperature, washed with MeCN, and no crystals were deposited at the bottom of the reaction bottle. Therefore, scandium-based MOF crystal materials cannot be generated without the structure-directing agent 1,2,4-triazole.

[0053] Example 6

[0054] At room temperature, 2,5-thiophenedicarboxylic acid (17.5 mg) and 1,2,4-triazole (10 mg) were dissolved in 2.5 ml of acetonitrile (MeCN) solution, and ultrasonicated for 1 h to fully mix them to obtain a white suspension S1. Hydrated scandium nitrate (46 mg) was dissolved in 1.8 ml of H2O, and ultrasonicated to fully mix them to obtain a transparent colorless clear liquid S2. The S1 solution and the S2 solution were mixed, 90 μL of concentrated nitric acid was added, and placed in an oven at 100 ° C for 48 h. Then it was taken out and cooled to room temperature, washed with MeCN, and no crystals were deposited at the bottom of the reaction bottle. Therefore, scandium-based MOF crystal materials cannot be generated when the reaction time is 48 h.

[0055] 2. Structural Characterization of Samples

[0056] like Figure 1 The optical microscope image of the scandium-based MOF crystal prepared in the above embodiment is shown, with the sample prepared in Example 3 as a typical example. The prepared scandium-based MOF presents a regular geometric shape and is a colorless transparent block crystal.

[0057] like Figure 2 The structure diagram of the scandium-based MOF crystal prepared in the above embodiment is shown in FIG. 3, and the sample prepared in Example 3 is used as a typical example. There are two independent Sc ions (Sc1, Sc2) in the MOF, both of which are hexacoordinated, and the coordination mode is as follows: Figure 2 (a) and Figure 2 As shown in (b). The four coordination sites of Sc1 are occupied by O on the carboxyl groups of four different ligands, and the other two coordination sites are occupied by a μ2-OH and a nitrate ion respectively; the six coordination sites of Sc2 are occupied by O on the carboxyl groups of four different ligands and two μ2-OH, forming an infinitely extended one-dimensional chain [Sc3(μ2-OH)3(CO2)4O6] n ,like Figure 2 (c) in these [Sc3(μ2-OH)3(CO2)4O6] nThe chains are further connected to each other through the ligand 2,5-thiophenedicarboxylic acid and nitrate ions to form a three-dimensional porous skeleton structure ( Figure 2 (d) and Figure 2 (e) in the figure.

[0058] 3. PXRD Characterization of Samples

[0059] like Figure 3 The PXRD pattern of the scandium-based MOF crystal prepared in the above embodiment is shown, with the sample prepared in Example 3 as a typical example. The experimental PXRD curve of the scandium-based MOF crystal is consistent with the simulated PXRD curve (simulated using single crystal structure data), indicating that the scandium-based MOF crystal is pure phase and does not contain other impurities.

[0060] 4. Stability analysis of samples

[0061] like Figure 4 The PXRD patterns of the scandium-based MOF crystals prepared in the above examples after being immersed in HCl and KOH aqueous solutions of different pH values ​​for 24 hours are shown, with the sample prepared in Example 3 being used as a typical example. The scandium-based MOF crystals can be stable in aqueous solutions ranging from pH=2 to pH=12, indicating that they have a wide range of pH stability.

[0062] like Figure 5 The PXRD patterns of the scandium-based MOF crystals prepared in the above examples after being immersed in water for different times are shown, with the sample prepared in Example 3 being taken as a typical example. At room temperature, the scandium-based MOF crystals can still maintain the integrity of their framework after being immersed in water for 1 month, indicating that they have good water stability.

[0063] like Figure 6 The PXRD spectra of the scandium-based MOF crystals prepared in the above examples after being immersed in different organic solvents for 24 hours are shown, with the sample prepared in Example 3 as a typical example. The scandium-based MOF crystals can stably exist in various organic solvents, indicating that they have excellent solvent stability.

[0064] like Figure 7 The thermogravimetric curve of the scandium-based MOF crystal prepared in the above embodiment is shown, with the sample prepared in Example 3 as a typical example. The scandium-based MOF crystal begins to decompose at 450° C., indicating that it has high thermal stability.

[0065] As reviewed, scandium-based MOF crystals have excellent thermal stability, water stability, solvent stability and wide pH stability.

[0066] 5. Gas adsorption properties of samples

[0067] Taking the sample prepared in Example 3 as a typical example, the prepared scandium-based MOF crystals were exchanged with anhydrous methanol for 3 days, 3 times a day, and then vacuum activated at 120°C for 24 hours to obtain activated scandium-based MOF. About 100 mg of activated scandium-based MOF was weighed and loaded into an adsorption tube of known mass, and the adsorption isotherms of C2H4, C2H6 and C3H6 were tested on a physical adsorption instrument. Assuming that He is not adsorbed at any temperature, He (99.999%) was selected to test the dead volume of the system. The test temperature points were 288K, 298K and 308K. About 920 mg of activated scandium-based MOF was weighed and filled into a stainless steel column (inner diameter 0.4 cm, length 15 cm), and helium was purged for 20 min at a flow rate of 10 mL / min. A dynamic adsorption penetration experiment of a three-component gas mixture of C2H6 / C3H6 / C2H4 (2 / 10 / 25, v / v / v) was carried out at 298 K.

[0068] like Figure 8 , Fig. 9 and Fig.10 The atmospheric pressure isothermal adsorption curves of C2H4, C2H6 and C3H6 of the activated scandium-based MOF crystals shown are at 288K, 298K and 308K, respectively. It can be seen that under extremely low pressure, the adsorption amount of C2H4 and C2H6 is very small, indicating that it is difficult for C2H4 and C2H6 to enter the scandium-based MOF pores under extremely low pressure, and below 0.8 bar, the adsorption amount of C2H4, C2H6 and C3H6 is not greatly affected by temperature. At room temperature (T = 298K), as the pressure increases, the scandium-based MOF crystals preferentially adsorb C3H6, then C2H6, and finally C2H4. Under 298K, 1 bar conditions, the adsorption amounts of C3H6, C2H6 and C2H4 are 98.6 cm 3 / g, 74.3cm 3 / g and 67.7cm 3 / g.

[0069] like Fig.11 Shown is the adsorption enthalpy Q of C2H4, C2H6 and C3H6 of the activated scandium-based MOF crystal st Based on the above atmospheric pressure isotherm adsorption curves, the adsorption enthalpies of C2H4, C2H6 and C3H6 at zero load are calculated to be Q st,C2H4 =41.8 kJ / mol, Q st,C2H6 =63.3 kJ / mol and Q st,C3H6 =83.7 kJ / mol. This shows that compared with C2H4, the framework structure of scandium-based MOF has stronger interaction with C3H6 and C2H6, and the amount of adsorbed C3H6 and C2H6 is larger. This phenomenon is consistent with the experimental results reflected by the atmospheric pressure isothermal adsorption curves of C2H4, C2H6 and C3H6.

[0070] like Fig.12 The adsorption selectivity of the activated scandium-based MOF crystal for mixed gas C2H6 / C2H4 (v / v, 1 / 9) at 298 K is shown. Based on the ideal adsorption solution theory (IAST), it is calculated to have a high C2H6 / C2H4 adsorption selectivity of 2.32, which is higher than some well-known C2H6-selective MOFs, such as TJT-100 (1.2) (Angew. Chem. Int. Ed., 2018, 57, 16067-16071.), NPU-2 (1.52) (J. Am. Chem. Soc., 2021, 143, 1485-1492.), Azole-Th-1 (1.46) (Nat Commun., 2020, 11, 3163.), JNU-2 (1.6) (J.Am.Chem.Soc., 2019, 141, 20390-20396.) and Zn-BPZ-TATB (1.7) (Angew.Chem.Int.Ed., 2023, 62, e202311654.).

[0071] like Fig.13 The adsorption selectivity of the activated scandium-based MOF crystal for mixed gas C3H6 / C2H4 (v / v, 2 / 5) at 298 K is shown. Based on the ideal adsorption solution theory (IAST), it is calculated to have a high C3H6 / C2H4 adsorption selectivity of 7.93, which is higher than some well-known C3H6-selective MOFs, such as PCP 1 (3.6) (Dalton Trans, 2018, 47, 9008-9013.), Cu-BTC (5.8) (J. Chem. Eng. Data, 2017, 62, 417-421.), Mg-MOF-74 (4.7) (Langmuir, 2011, 27, 13554-13562.), spe-MOF (7.7) (Angew. Chem. Int. Ed., 2021, 60, 16521-16528.).

[0072] like Fig.14 The figure shows the penetration curve of the activated scandium-based MOF crystal at 298K with a three-component gas mixture of C2H6 / C3H6 / C2H4 (2 / 10 / 25, v / v / v). The results show that C2H4 penetrates first, with a penetration time of 43 minutes, and the desired high-purity C2H4 is produced at 53 minutes with a yield of 13.04L / kg; compared with C2H4, C2H6 has a stronger interaction with the scandium-based MOF framework (Q st,C2H4 =41.8 kJ / mol st,C2H6 ​=63.3 kJ / mol), so it was retained for a while, and C2H6 began to penetrate at 59 min; since the interaction between C3H6 and the scandium-based MOF framework is the strongest (Q st,C2H4 =41.8 kJ / mol st,C2H6 =63.3 kJ / mol st,C3H6 =83.7 kJ / mol), and C3H6 did not reach the breakthrough point until 155 min. This shows that scandium-based MOF can well separate C2H4 and C2H6, obtain high-purity C2H4 and recover C3H6 in one step.

[0073] like Fig.15 , Fig.16 Shown are the analytical curves of the activated scandium-based MOF crystals after adsorption of a saturated three-component gas mixture (C2H6 / C3H6 / C2H4 (2 / 10 / 25, v / v / v)) and the analytical curves after adsorption of saturated C3H6. Since C3H6 is another target gas that needs to be purified from the MTO product, after the fixed bed column reaches the equilibrium concentration, the adsorption saturated scandium-based MOF crystals are subjected to a desorption experiment at 338K with helium (4mL / min) to produce pure C3H6. The experiment shows that the scandium-based MOF crystals are easily regenerated, among which C2H4 and C2H6 are more quickly decomposed than C3H6. After 16 minutes, high-purity C3H6 is decomposed with a yield of 28.01L / kg.

[0074] The above experimental results show that the scandium-based MOF crystal material of the present invention preferentially adsorbs C3H6, then C2H6, and finally C2H4 at room temperature and pressure, has good C3H6 / C2H4 and C2H6 / C2H4 separation performance, can well separate C2H4 and C2H6 to obtain high-purity C2H4 and recover C3H6, and is expected to achieve efficient separation of C2H4 and C3H6 from MTO mixture.

[0075] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.​​

Claims

1. A stable scandium-based MOF crystalline material, characterized in that: Its chemical formula is: {[Sc3(OH)2(Tdc)3(NO3)]·H2O} ∞ .

2. The scandium-based MOF crystal material according to claim 1, characterized in that: The scandium-based MOF crystal material has a microporous structure, which is composed of [Sc3(μ2-OH)3(CO2)4O6] n The inorganic metal chain is self-assembled by connecting with the organic ligand 2,5-thiophenedicarboxylic acid and nitrate ion.

3. The scandium-based MOF crystal material according to claim 2, characterized in that: The [Sc3(μ2-OH)3(CO2)4O6] n There are two independent Sc ions in the inorganic metal chain, namely Sc1 and Sc2, both of which are hexacoordinated. The six coordinated oxygen atoms of Sc1 come from four different 2,5-thiophenedicarboxylic acid ligands, one μ2-OH and a nitrate ion; the six coordinated oxygen atoms of Sc2 come from four different 2,5-thiophenedicarboxylic acid ligands and two μ2-OH.

4. The scandium-based MOF crystal material according to claim 1, characterized in that: The scandium-based MOF crystal material belongs to the monoclinic system and the I2 / m space group.

5. The scandium-based MOF crystal material according to claim 1, characterized in that: The crystallographic data of the scandium-based MOF crystal material are: unit cell parameters: α=90°, β=96.642(3)°, γ=90°, Z=4.

6. A method for preparing a scandium-based MOF crystal material according to any one of claims 1 to 5, characterized in that: The method is directly synthesized by solvent thermal reaction of 2,5-thiophenedicarboxylic acid and metal Sc, which specifically comprises the following steps: (1) Add 17.5 mg of the organic ligand 2,5-thiophenedicarboxylic acid and 10 mg of the template 1,2,4-triazole into 2.5 ml of acetonitrile and perform sonication for a period of time to fully mix the mixture, which is recorded as the first solution; (2) Dissolve 46 mg of hydrated scandium nitrate in 1.8 ml of H2O, referred to as the second solution; (3) mixing the first solution and the second solution, and then adding 60 to 90 μL of concentrated nitric acid to obtain a transparent mixed solution; (4) placing the mixed solution in an oven for solvothermal reaction to obtain the scandium-based MOF crystal material.

7. The method according to claim 6, characterized in that The solvent thermal reaction temperature was 100°C and the reaction time was 72 h.

8. Use of the stable scandium-based MOF crystal material according to any one of claims 1 to 5 or the scandium-based MOF crystal material prepared according to any one of claims 6 and 7 in separating light hydrocarbon mixtures and purifying C2H4.

Citation Information

Patent Citations

  • Preparation and application of stable metal organic framework material based on 4-linked scandium trinuclear cluster

    CN115044053A

  • Scandium metal organic framework material as well as preparation method and application thereof

    CN117417543A

  • Lanthanum-based MOF crystal material, preparation method and application method in natural gas decarburization

    CN118955923A

  • Metal organic frameworks polymorphism for adsorption profile tuning

    WO2024160984A1